Adipose derived stem cells protect skin flaps against ischemia-reperfusion injury - Reichenberger, Matthias; Heimer, Sina Franziska; Schaefer, Amelia; Gebhard, Martha-Maria; Germann, Günter; Leimer, Uwe; Köllensperger, Eva; Müller, Wolf C. (Stem cell reviews and reports, 2012)
BackgroundAdvances in the treatment of ischemia- reperfusion injury have created an opportunity for plastic surgeons to apply these treatments to flaps and implanted tissues. We examined the capability of adipose derived stem cells (ADSCs) to protect tissue against IRI using an extended inferior epigastric artery skin flap as a flap ischemia- reperfusion injury (IRI) model.MethodsADSCs were isolated from Lewis rats and cultured in vitro. Twenty- four rats were randomly divided into three groups. Group I was the sham group and did not undergo ischemic insult; rather, the flap was raised and immediately sutured back (non-ischemic control group). Group II (ischemia control) and group III (ADSCs treatment) underwent 3 h of ischemic insult. During reperfusion group III was treated by intravenous application of ADSCs and group II was left untreated. Five days postoperatively, flap survival and perfusion were assessed. Microvessel density was visualized by immunohistochemistry and semi- quantitative real-time polymerase chain reaction addressed differential gene expression.ResultsTreatment with ADSCs significantly increased flap survival (p < 0.001) and flap perfusion (p < 0.001) when compared to the control group II. Microvessel- density in ADSCs treated group was not significantly increased in any group. No significant differences showed the comparison of the experimental group III and the sham operated control group I. ADSCs treatment (Group III) was accompanied by a significantly enhanced expression of pro-angiogenic and pro-inflammatory genes.ConclusionOverall, our study demonstrates that ADSCs treatment significantly enhances skin flap survival in the aftermath of ischemia to an extent that almost equals surgical results without ischemia. This effect is accompanied with a pronounced and significant angiogenic response and an improved blood perfusion.
Gesehen am 03.05.2018